ANALISIS HARGA POKOK PRODUKSI PADA MEBEL JEPARA ANUGRAH IMANUEL - Alvinda Viadolorosa Tambajong; Longginus Gelatan (CV. Adiba Aisha Amira, 2025)
The purpose of this study was to analyze the correct cost of goods produced and the level of profit obtained for each product at Anugrah Imanuel Jepara Furniture. This research is descriptive research, the data used is primary data collected through interviews and documentation. The results of this study indicate that the cost of goods produced using the full costing method is Rp 482,560 door leaf products, Rp 387,778 window leaf products, Rp 284,010 door frame products and Rp 247,674 window frame products. And for the profit level using the Gross Profit Margin method, the door leaf product is 43%, the window leaf product is 14%, the door frame product is 5% and the window frame product is 17%. Based on the research results that the calculation of the cost of production using the full costing method shows that the door leaf has the highest cost of production due to the use of a lot of plank wood, difficulty in assembly and finishing, and high factory overhead costs, while the window frame has the lowest cost of production